Evaluation of electronic libraries - Tiwari, Aravind (A. P. H. Publishing Corporation, 2002)
Contents of material: 1/ Automation in libraries. 2/ Library automation and networks. 3/ Coordination. 4/ Interlibrary lending. 5/ Information service. 6/ Inline interactive systems. 7/ Prensentation of bibliographic information. 8/ Online catalogues. 9/ Effect of automation. 10/ Problems of library automatio systems.